Inovasi Disruptif Gojek Indonesia - Fahmy Radhi; Fani Pramuditya (Politeknik Negeri Batam, 2021)
This study analyzes Gojek's business as a part of disruptive innovations based on the original theory and principles developed by Clayton Christensen and discusses factors that driven Gojek to become disruptive innovation. In-depth interviews with Gojek’s employees were conducted to collect the data. The research finds that Gojek can be categorized as a disruptive innovation that successfully transformed the market. Innovation is the core culture of the organization, which leads the company to disrupt the market successfully. Several internal and external factors, such as leadership, organizational structure and culture, external funding, undeveloped law, customer needs, and internet penetration, have proven to support and accelerate Gojek as a disruptive innovation.